Assessment on the treatment of nitrogen contaminant by constructed wetland exposed to different concentrations of graphene oxide. (1st March 2022) - Yan, Chunni; Huang, Juan; Wang, Yaoyao; Lin, Xiaoyang; Cao, Chong; Qian, Xiuwen
Abstract: The environmental effect of two-dimensional carbon-based graphene oxide (GO) is an emerging worry as it becomes more widely used. The present work investigated the effects of GO (0.5 and 5 mg/L) on nitrogen transformation in constructed wetlands (CWs). GO could be effectively captured by CWs, but it was harmful to nitrogen removal. GO delayed dynamic time of nitrogen transformation with slight increases in ammonia and nitrate effluent concentrations, resulting in nitrogen removal reducing from 59.24% to 51.51–54.12% (p < 0.05). GO showed the selective influence on key enzyme involved in nitrogen transformation. It caused 33% and 37% inhibitions on ammonia monooxygenase (at 0.5 and 5 mg/L GO) and nitrate reductase (only at 0.5 mg/L GO), but 153% stimulations on urease at 5 mg/L GO. The evidence at molecular level showed that GO reduced abundances of amoA, anammox, and nirS gene, which was determined by GO concentration, contact time, and target gene. 5 mg/L GO produced more obvious reductions on relative abundances of denitrification genes ( narG, napA, nirK, qnorB, and nosZ ) after 120 days. The shifts in microbes related to nitrogen transformation were also observed after GO feeding, but collaborative microbial pathways were still presented including ammonia-oxidizing bacteria ( Nitrosomonas and Nitrosospira ), nitrite-oxidizing bacteria ( Nitrospira ), denitrifying bacteria ( Sphingomonas, Arenimonas, Rhodopseudomonas, Rhodanobacter ), heterotrophic nitrification aerobic denitrification bacteria ( Bacillus, Acidovorax, Dechloromonas, Acidovorax ), and nitrogen-fixing bacteria. The denitrification was rate-limiting TN removal process due to insufficient carbon sources and dominant aerobic environment in CWs. The present work deepened understanding of variations in ecological functions of CWs when they encountered nano-pollution. Graphical abstract: Image 1 Highlights: Graphene oxide delayed dynamic time of nitrogen conversion and decreased total nitrogen removal. Graphene oxide negatively influenced nitrification and denitrification enzyme, while it positively regulated urease. Graphene oxide reduced abundances of nitrogen functional gene depending on its concentrations, time, and target gene. The multiple microbial pathways for nitrogen removal were evidenced in the presence of graphene oxide.